Prevalence of hypertension and related risk factors in older Chinese population: a meta-analysis - Wang, Zicheng; Wang, Shengjie; Lin, Haiyan; Wang, Congling; Gao, Da (Frontiers in Public Health, 2024)
Objective:Hypertension is the most challenging public health problem worldwide and seriously affects human health. To date, there are no epidemiological studies on the prevalence of and risk factors for hypertension among older people in mainland China.We conducted a meta-analysis of the prevalence and risk factors of hypertension among the older population in mainland China. We searched Chinese and English databases for Chinese and English literature on hypertension epidemiology published between 2000 and 2022, and hypertension data among the older population were extracted from the included literature. A meta-analysis was performed using a random-effects model (I 2 > 50%) with 95% confidence intervals for the forest plots. Data were processed using RevMan 5.3. Forty-nine publications (with data from 84,429 samples) met the evaluation criteria and were included in this study.We found that the total prevalence of hypertension was 47%. The total prevalence rate of the older population in China from 2000 to 2010 was 50%, and the prevalence rate from 2011 to 2021 was 45%, with no significant differences. The total prevalence in Central China was the highest (59%). There was no significant correlation between the prevalence rate of the older population, sex, and urban or rural areas.Hypertension is common among the older population in China, and its control rate is low. Therefore, effective prevention and treatment measures, as well as education, should be formulated to improve the diagnosis and treatment of hypertension in the older population.